TRADISI SEMBAHYANG CIOKO (鬼節Guǐ Jié) DI PAN KHO BIO, BOGOR CIOKO (鬼節Guǐ Jié) TRADITION IN PAN KHU BIO, BOGOR - Ni Putu Diah Wahyuni; C. Dewi Hartati (Fakultas Sastra Universitas Darma Persada, 2020)
Cioko as one of the ceremonial traditions in Chinese culture has a meaning as a sense of devotion to the ancestors for the Chinese community. They believe that in this world humans do not live alone and their ancestors can still witness from a different realm. Prayers are performed to remember the ancestors and so that the ancestors are calm in their nature. This prayer also aims to ask for protection from their ancestors. Similarly, the Chinese in Bogor held the Cioko ceremony at a temple in Bogor, namely Pan Khu Bio. In addition to the Chinese community who held the Cioko celebration, the people who lived around Pan Kho Bio also helped during Cioko. Starting from preparation, helping decorate the temple to cleaning the temple after Cioko finished. Despite differences in beliefs, residents help each other at the temple and form a social bond.